Chronic Social Defeat Stress Shifts Peripheral Circadian Clocks in Male Mice in a Tissue-Specific and Time-of-Day Dependent Fashion. Issue 2 (April 2022) - Kong, Xiangpan; Ota, Simone M.; Suchecki, Deborah; Lan, Andy; Peereboom, Anouk I.; Hut, Roelof A.; Meerlo, Peter
Uncontrollable stress is linked to the development of many diseases, some of which are associated with disrupted daily rhythms in physiology and behavior. While available data indicate that the master circadian pacemaker in the suprachiasmatic nucleus (SCN) is unaffected by stress, accumulating evidence suggest that circadian oscillators in peripheral tissues and organs can be shifted by a variety of stressors and stress hormones. In the present study, we examined effects of acute and chronic social defeat stress in mice and addressed the question of whether effects of uncontrollable stress on peripheral clocks are tissue specific and depend on time of day of stress exposure. We used mice that carry a luciferase reporter gene fused to the circadian clock gene Period2 (PER2::LUC) to examine daily rhythms of PER2 expression in various peripheral tissues. Mice were exposed to social defeat stress in the early (ZT13-14) or late (ZT21-22) dark phase, either once (acute stress) or repeatedly on 10 consecutive days (chronic stress). One hour after the last stressor, tissue samples from liver, lung, kidney, and white adipose tissue (WAT) were collected. Social defeat stress caused a phase delay of several hours in the rhythm of PER2 expression in lung and kidney, but this delay was stronger after chronic than after acute stress. Moreover, shifts only occurred after stress in the late dark phase, not in the early dark phase. PER2 rhythms in liver and WAT were not significantly shifted by social defeat, suggesting a different response of various peripheral clocks to stress. This study indicates that uncontrollable social defeat stress is capable of shifting peripheral clocks in a time of day dependent and tissue specific manner. These shifts in peripheral clocks were smaller or absent after a single stress exposure and may therefore be the consequence of a cumulative chronic stress effect.